Legal aspects of applying indexes and e-management in evaluating the publication activity of scientists - R. O. Omorov (E-Management, 2020)
Scientometry methods meet the requirements of digitalization and e-management of the science, development due to the widespread use of mathematical methods of information processing. To assess the scientific productivity of scientists and specialists in scientometrics, various indicators are used, the most common of which is the Hirsch index or h-index. The Hirsch index is calculated from the number of citations of the researcher’s works included in a certain database.For CIS countries, an important database of scientific and educational publications is the database of the Russian Scientific Citation Index (RSCI). One of the problems with using the Hirsch index is the compliance of assessments with copyright rules. The Hirsch index shows the comparative effectiveness of the work of a scientist or team of scientists. But as it is not difficult to see, according to the Hirsch index counting indicators for the RSCI databases, for individual scientists their contribution and participation in collective publications and their citations are not taken into account. It is proposed to introduce a modified Hirsch index, called the Hirsch index “plus” or h +, which is calculated on the basis of dividing the usual number of citations of a particular publication by the number of co-authors of the cited publication, which will not cause difficulties in calculating h + indices, using the algorithm for determining the Hirsch index itself. Such an indicator corresponds to copyright rules, takes into account the interests of co-authors from the point of view of copyright and more accurately assesses the effectiveness of the work of a particular author when comparing the work of scientists.Modern scientometrics is a necessary tool for research on the development of science, forecasting and managing its development, some of the indicators of which are citation indices, in particular, the most common in practice is the Hirsch index, and the Hirsch “Plus” index and other modifications to take into account the individual contributions of scientists and specialists. Each of the existing modifications of scientometric indices can be used to investigate the publication activity of scientists and specialists depending on the specifics of the tasks set, taking into account the complexity and convenience of calculating specific indexes.